2019
DOI: 10.1038/s41598-019-54313-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signatures associate with disease severity in children with Mycoplasma pneumoniae pneumonia

Abstract: Host immune response may be involved in the pathogenesis of children Mycoplasma pneumoniae pneumonia (MPP). In the current study, we investigated the alterations of cytokines levels among control, mild MPP and severe MPP children to determine whether cytokine signatures associate with MPP and correlate with disease severity. We measured 13 cytokines in bronchoalveolar lavage fluid (BALF) of 88 children with MPP and 26 children with foreign body aspiration (FB) using a Luminex system. Linear discriminant analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
6
24
1
Order By: Relevance
“…Our findings on the Mp -specific Th1 cell response are corroborated by previous observations in animal models suggesting that Th1 cells contribute to inflammatory lesions in mycoplasma pneumonia ( 1 , 2 , 15 ), and clinical studies in children and adults where the IFN-γ response correlated with the disease severity and/or radiological changes in CAP associated with Mp ( 16 18 ). Furthermore, we expand these observations by revealing Mp -specific T EM cells as the major Th1 cell compartment associated with more severe disease.…”
supporting
confidence: 90%
“…Our findings on the Mp -specific Th1 cell response are corroborated by previous observations in animal models suggesting that Th1 cells contribute to inflammatory lesions in mycoplasma pneumonia ( 1 , 2 , 15 ), and clinical studies in children and adults where the IFN-γ response correlated with the disease severity and/or radiological changes in CAP associated with Mp ( 16 18 ). Furthermore, we expand these observations by revealing Mp -specific T EM cells as the major Th1 cell compartment associated with more severe disease.…”
supporting
confidence: 90%
“…In our study, the levels of IL-6, IL-10, IL-17A, TNF-α and the number of in ammatory cells (including neutrophils, macrophages and lymphocytes) in BALF of children with severe pneumonia were signi cantly higher than those of children with mild pneumonia. These results were similar to previous study 8,26 . Interestingly, compared with children with mild pneumonia, the percentage of macrophages in BALF of children with severe pneumonia was decreased relatively, while the percentage of neutrophils increased signi cantly.…”
Section: Discussionsupporting
confidence: 93%
“…C-reactive protein (CRP) and procalcitonin (PCT) are often used to re ect the severity of pneumonia, but their application in clinical practice is limited due to their poor speci city and delayed response to in ammation. Studies have shown that the cytokine signals in patients with severe and mild pneumonia are different 8,9 . Studies have also pointed out that in children and adults with pneumonia, serum cytokine signals (mainly IL-6 and IL-10) help to identify the pathogen 10,11 , evaluate the severity and prognosis of pneumonia [12][13][14] .…”
mentioning
confidence: 99%
“…Indeed, Mp-specific CD4 + T cell responses are important for exacerbated inflammation (Dobbs et al, 2009). For example, Yang et al have shown that an elevated Th1/Th2 ratio is associated with disease severity in mycoplasma pneumonia in humans (Yang et al, 2019). Other reports have shown increased levels of IFN-g in the serum of children with mycoplasma pneumonia (Fan et al, 2015) or refractory mycoplasma pneumonia (Wang et al, 2014;Zhang et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%